(untitled) (Farabi Journal of Social Sciences, 2024)
This research on training needs assessment aims to identify the technical, management, and leadership skills and competencies that are lacking among elected Union Parishad members in Bangladesh. The study used both qualitative and quantitative approaches and was conducted in the Chandpur District. Four unions in three Upazilas were randomly selected from the EALG project list, and 52 Chairmen, Members, and Women were interviewed. Additionally, seven Key Informant Interviews (KIIs) were conducted with relevant professionals. The report revealed deficits in training for Union Parishad chairmen and members. Since the functions of chairmen and members differ, their training needs also vary. Members and chairs should prioritize training in ICT, Good Governance, and Service. Strategy, budget, and audit training should be the second priority for chairmen while training on citizens’ welfare and service-related cross-cutting issues ranks third for members and fourth for chairmen quantitatively. Qualitative interviews underscored the importance of training. Notably, the combined results of chairmen and members placed training related to the general functions and activities of chairmen and members sixth, while experts feel that it is vital. Most participants recommended a seven- to 10-day district-level training with a local government or rural development organization field trip. Local government experts, especially those with experience in Union Parishads, are recommended for providing the training. Keywords: TNA, Representative, Union Parishad, Local government, Bangladesh. Information about authors: Md. Ruhul Amin (Corresponding Author) – PhD, Associate Professor, Department of Public Administration, Comilla University, (Comilla, Bangladesh, e-mail: rubelcou@gmail.com) Md. Nur Uddin Hossain – Master’s degree, Comilla University, (Comilla, Bangladesh, e-mail: nuruddin7654@gmail.com)